Menggagas Perencanaan Kurikulum Sekolah Unggul - Zainur Roziqin (AS-SABIQUN, 2019)
This paper aims to find out how the curriculum and how the actual curriculum planning is offered by superior schools. Creating a quality curriculum for superior schools is very important, because the curriculum is a door to guarding the direction of educational goals to be brought, a leader of school institutions and other institutions must have the consideration and understanding of competent management to get a quality and superior curriculum. the initial stage in the management function that must be mastered by the leadership of the school institution management is the planning function which becomes the initial foundation for making the curriculum in line with the vision and mission of the institution. Therefore curriculum planning in superior schools is very important in order to get the real label that schools that use planning in their curriculum are truly superior schools. The results of the analysis of the authors describe that some of the planning used by superior schools is to emphasize the formation of quality.